Training, career development, and environment to improve employee performance with work motivation as a mediating variable - Triyanto Dartono; Pamuji Gesang Raharjo; Etty Nurwati (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to examine the influence of training, career development, and the work environment on employee performance, with work motivation serving as a mediating variable. A quantitative research design was employed using survey data collected through structured questionnaires from 215 respondents selected using a saturated sampling technique. The proposed relationships were analyzed using Structural Equation Modeling (SEM). The findings indicate that training, career development, and the work environment each have a positive and significant effect on work motivation. Training also has a direct positive effect on employee performance, whereas career development and the work environment do not directly influence performance. In contrast, work motivation has a positive and significant effect on employee performance and significantly mediates the relationships between training, career development, and the work environment with employee performance. These findings underscore the pivotal role of work motivation in translating human resource development practices and workplace conditions into improved employee performance. The study contributes to the human resource management literature by demonstrating the importance of motivational mechanisms in strengthening the effectiveness of organizational development initiatives and offers practical insights for designing integrated strategies to enhance employee performance. Keywords:Training; Career Development; Work Environment; Work Motivation; Employee Performance